Os usos políticos da narrativa mítica em Luciano de Samósata: aspectos do regime de memória romano (séc. II D. C) - Arantes Junior, Edson (2014)
Lucian of Samosat was an important interpreter of the Roman Empire, his writings were about a varied of topics. People who study about this writer focused on two possibilities for understanding his political stance: on one hand, there are authors who consider he is disconnected from his time and sociopolitical context; on the other hand, there are those who see him as a political activist opposed to Rome. In this Thesis, we consider that Lucian has an ambiguous position, since he identifies himself as Syrian, underscores his entire Hellenic education and criticizes aspects of Roman political culture. However, we believe that he was aware of the benefits that the empire brought all dominated peoples. Thus, we can say that he was a writer who collaborated with the maintenance of the imperial system. To prove this hypothesis, we analyze his famous satirical dialogues, which were often disregarded by his interpreters. Known for combining the dour philosophical dialogue with sarcastic comedy, we understand that the writer intended to produce laughter, which would turn to the mobilization of thought. We restrict our investigation to the dialogues that use mythology as subject. The myths were thought as components of a cultural memory and thus are presented within the limits of the Roman memory system. This selection was formally organized on topics related to political power and its everyday manifestations. Thus, we are concerned with the Lucianic representation of assemblies, tyrants and the relations of the deities among them and especially with Zeus. We understand that Lucian did a thorough exegesis of his reality, highlighting and criticizing abusive postures. In his dialogues, we can see other possible dimensions of interpretation of political power in the Roman Empire.